Health governance after Brexit: street ethnography and elite interviews, 2019-2021 - Hervey, Tamara Katherine (UK Data Service, 2021)
Street ethnography was conducted through street interviews in the North of England (Sheffield, Rochdale and Rotherham) and Northern Ireland (Newry, Derry/Londonderry) designed to elicit public understandings of accountability for post-Brexit realities, and hence legitimacy of post-Brexit governance. Ethnographic street interviews are useful for capturing a diffuse public ‘mood’ in particular locations identified as important for expectations about post-Brexit health governance - the ‘left behind’. The term ‘ethnographic’ means these interviews occur in ‘unstructured’ public spaces, like shopping centres or high streets, and are based on unobtrusive questions about abstract concepts. Their aim is to capture intuitive conceptions of key ideas (‘what do you think of when you hear the word accountability?’, for example), in a context where research participants are more likely to give answers reflecting their intuitive expectations and views in a way that more structured methods like focus groups do not. The metaphors people use to describe abstract or complex concepts (such as accountability for post-Brexit governance of health and the NHS) reveal how they frame, experience and understand the world, and key concepts related to it. Transcripts and field notes from the ethnographic interviews have been thematically coded. This contribution is particularly distinctive in political science studies, which tend not to examine ‘everyday’ conceptions of accountability in a broader context of legitimacy. The collection of data from elite stakeholders relevant to the project was carried out in the first instance through semi-structured interviews. Two interviewers (TH and MW) conducted the interviews with co-producer stakeholder participants in their workplaces in England (predominantly London, but also Leeds and Alton, Kent) and one interviewer (MF) conducted the interviews with participants in Northern Ireland/ROI (predominantly Belfast and Dublin). Language such as 'a red, white and blue Brexit' or 'Brexit means Brexit' allows for an array of ideas about Brexit to be projected onto the process of the UK leaving the EU and what it means. The EU is not just a political organisation, it is also a legal organisation. Leaving the EU means agreeing a new legally expressed relationship for now and for the future. It also means new UK laws, such as a Trade Act and Immigration Act. We are investigating the (legal) language of Brexit, and comparing how elites and ordinary people understand it. We are doing that in the context of a topic that matters a great deal to the general public: health and the NHS. We want to analyse what the new laws will mean for patients, for NHS staff, for drugs, medical devices and equipment, blood and organ donation, and for laws that affect our health, like food safety and tobacco regulation. To make that legal analysis useful, we will work with some specific groups, all of whom have expertise in key areas impacted by Brexit, to help us understand what scenarios the people they work with or represent are facing. These groups include Kidney Care UK; the Faculty of Public Health; and the Colleges of Midwives in the UK and the Republic of Ireland. Once we have done that, we will find out how the general public understand what is happening to health and the NHS post-Brexit. Are people happy with the changes? Who do they think is responsible and should be responsible? Do they think the new law is legitimate? We will work in two places that represent different issues in a post-Brexit world: the north of England, and Northern Ireland. The north of England is a 'left-behind' region economically, and this is one explanation given for its pattern of Leave voting. Northern Ireland faces special challenges post-Brexit, because it shares a land border with the rest of the EU. Health services have been shared in the north of the island of Ireland for a long time, and EU law has helped to support that. We will carry out street interviews, to understand how ordinary people think about abstract ideas like Brexit and accountability. We will use the information from our legal analysis to ask people what they think about what the new laws mean - for patients, for NHS staff, and so on. Finally, we will compare the language that the law uses, and that experts use, with the everyday language used by the general public. When we talk about abstract things, we often use metaphors, like 'red, white and blue Brexit'. Examining metaphors will help us to understand how people feel, and whether the general public feel the same as experts. Metaphors will help us find out if there are gaps between how people feel about the new post-Brexit laws on health and the NHS, and what those laws achieve. This will help us understand whether post-Brexit law enjoys social legitimacy - and if not, why not. That could - and should - inform policies about what to do about it.